The influence of ppb levels of chloride impurities on the stain-induced corrosion cracking and corrosion fatigue crack growth behavior of low-alloy steels under simulated boling water reactor conditions. (July 2016) - Seifert, H.P.; Ritter, S.
Highlights: Chloride effects on strain-induced corrosion cracking and corrosion fatigue crack growth in RPV steels. ppb-levels of chloride increase strain-induced corrosion cracking initiation susceptibility in boiling water reactor environment. No effect of chloride on subsequent strain-induced corrosion crack growth in boiling water reactor environment. Acceleration of corrosion fatigue crack at intermediate corrosion potentials and low loading frequencies only. Abstract: The effect of chloride on the strain-induced corrosion cracking (SICC) and corrosion fatigue (CF) crack growth behaviour in low-alloy reactor pressure vessel steels was evaluated under simulated boiling water reactor normal water chemistry conditions by slow rising load and cyclic constant load amplitude tests with air fatigue pre-cracked fracture mechanics specimens. Chloride in the ppb level range increased the SICC initiation susceptibility, but had almost no effect on the subsequent SICC and CF crack growth. A strong effect of chloride addition of 100 ppb on CF crack growth was observed at intermediate corrosion potentials and very low loading frequencies only.